KEKERASAN DALAM RUMAH TANGGA DALAM PERSPEKTIF GENDER - Ikwanuddin Harahap (Jurnal AL-MAQASID: Jurnal Ilmu Kesyariahan dan Keperdataan, 2018)
Everyone wants the happy family. Family is the safety home for all member of the family; father, mother and their children. But in fact, the theory is different with the fact. In other hand, the family can be “ the hell” for husbands, wives or childen. It is caused the violence done by one of the family member, especially done by the husband to his wive or Kekerasan Dalam Rumah Tangga (KDRT). There are many kinds of violences in family, namely physical violence such as beating, slaping, kick, biting, marital rape, etc., and non- physical violence such as intimidation, threat, terror, etc.  This article tries to analysis the KDRT on gender perspective. The writer uses the mainstream analysis on gender, namely marginalization, subordination, violence, stereotype, and double burden.